Synthesis and structural characterization of rare-earth iron garnet: (Sm, Gd)3Fe4.9Al0.1O12 - Santos J.M. (2021)
In this work, we synthesized and characterized structurally the rare earth iron garnets R3Fe4.9Al0.1O12 (R = Sm, Gd) by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman microscopy, and magnetization. The samples were synthesized using the co-precipitation synthesis method and calcined at a temperature between 500 and 900 °C stepwise 100 °C. Sm3Fe4.9Al0.1O12 and Gd3Fe4.9Al0.1O12 powder samples were indexed with a garnet cubic structure belonging to the Ia3?d space group. Structural analyzes indicate that the inclusion of Al instead of Fe slightly decreases the temperature of magnetic ordering. Crystallite sizes calculated from Scherrer's equation and Williamson-Hall method from XDR were 118 nm and 103 nm for Sm3Fe4.9Al0.1O12 and Gd3Fe4.9Al0.1O12 respectively. The SEM analysis results revealed that the particles were formed with average sizes of 469 nm to Sm3Fe4.9Al0.1O12 and 295 nm to Gd3Fe4.9Al0.1O12, both samples present grains with homogeneous morphology and heterogeneous size. Raman spectroscopy shows the presence of vibrational modes at room temperature of the symmetry to the garnet structure, as well as, the evolution of one mode with the temperature near the Néel temperature (TN), which is interpreted due to spin-phonon coupling in both samples. Magnetization measurements confirm that the compounds display a ferrimagnetic order with a TN at 552.0 K to Sm3Fe4.9Al0.1O12 and 547.0 K to Gd3Fe4.9Al0.1O12 which is slightly smaller than TN from undoped ferrites garnets. © 2021 Elsevier Ltd and Techna Group S.r.l.